Alterações de desenvolvimento dentário em pacientes nascidos com fissuras labiopalatinas - Cavalcante, Bianca Golzio Navarro (2020)
Individuals born with cleft lip and palate (CLP) have considerably more dental anomalies outside the cleft area than individuals born without clefts. Understanding the association between CLP and dental development anomalies can help to clarify the mechanisms of development under control of genetic and environmental factors, establish new classifications and determine risk factors. For this, we have focused not only on the prevalence of dental anomalies, but also on their distribution in different types of clefts, to help increase homogeneity and speed up the identification of genes. MMP2 is a metalloproteinase we have shown to be involved in pathologies that involve the dentin-pulp complex. The aim of this study is to use dental development as a tool to subphenotype CLP and investigate the association of MMP2 with dentin-pulp complex anomalies in individuals born with clefts. To investigate these associations, we examined 290 individuals and several clinical features, such as cleft completeness or incompleteness, laterality, and presence of dental anomalies were used to assess each individual‟s cleft status. We tested the MMP2 single nucleotide polymorphism rs9923304. Chi-square and Fisher‟s exact tests were performed (α = 0.05).Statistically significant differences between individuals with and without talon cusp was observed for the frequency of MMP2 less common allele (p=0.04). All individuals born with CLP had alterations of the dentition, and a quarter to half of the individuals had alterations of the internal anatomy of their teeth. Dental malposition, dilaceration and taurodontism are anomalies that can be considered as part of the cleft phenotype for future association studies. The MMP2 gene may be a modifier of dental development in individuals affected by CLP.